Is leader innovation a challenge or a burden for employees? The perspective of affective events - Shiwei Zhang; Chuqi Hang; Xiaojing Shao; Li Zhang (Acta Psychologica)
The importance of innovation has lit scholars' passion to figure out how to encourage innovative behavior, while its outcomes have been largely overlooked. Meanwhile, prior studies have focused on employees as the innovator and ignored that leaders are even more responsible to innovate. To understand employees' emotional and behavioral reactions to leader innovative behavior, this study drew on the affective events theory and regulatory focus theory and constructed a dual pathway model to illustrate the double-edge sword effects of leader innovation. We collected data from 219 full-time employees through three rounds of surveys and conducted statistical analysis and hypothesis testing using Mplus 8.3. The results revealed a significant positive effect of leader innovative behavior on employee work engagement through harmonious passion, which is moderated by employee promotion focus, such that the positive effect is stronger when promotion focus is higher. The results also indicated that leader innovative behavior is positively related to employee work withdrawal via job anxiety and prevention focus moderate the relationship, such that the positive effect is stronger when prevention focus is higher. This study reveals the double-edge sword effect of leader innovation on employee work behaviors from an affective event perspective, which provides theoretical and practical guidance for leaders and organizations in promoting the positive effect while reducing the negative effect of leader innovative behavior.